Frequency analysis of multidrug resistance-1 gene transfer into human primitive hematopoietic progenitor cells using the cobblestone area-forming cell assay and detection of vector-mediated P-glycoprotein expression by rhodamine-123 - Frühauf, Stefan; Breems, D. A.; Knaän-Shanzer, S.; Brouwer, K. B.; Haas, Rainer; Löwenberg, Bob; Nooter, K.; Ploemacher, R. E.; Valerio, D.; Boesen, J. J. B. (Human gene therapy, 1996)
Transfer of the multidrug resistance-1 (MDR1) gene into hematopoietic progenitor cells may reduce myelotoxicity of MDR1-related cytotoxic agents and therefore allow dose intensification. Mobilized peripheral blood progenitor cells (PBPC) can be obtained in ample quantity and are a suitable target cell population. CD34-selected PBPC samples (n = 6) were transduced with cell-free supernatant (SNT) of a cell line producing recombinant retrovirus containing the human MDR1 gene. Limiting-dilution long-term cultures were employed that allow continuous monitoring of stroma-adherent cobblestone areas (CA) and comparison of their frequency in a 5-log range over time. MDR1 provirus integration in CA-containing wells followed single-hit kinetics. According to Poisson statistics, proviral DNA was contained in 22% of unselected cobblestone area-forming cells (CAFC) at week 6, which represent primitive hematopoietic precursors. In comparison, 1.0 ± 0.44% (mean ± SEM) of week-6 CAFC were expressing P-glycoprotein at sufficient levels to convey vincristine resistance, suggesting low expression of the retroviral vector or splicing of the vector-drived mRNA in hematopoietic progenitor cells. Next we analyzed lineage-committed progenitors. The proviral DNA was detectable in 20-66% of colony-forming units granulocyte-macrophage (CFU-GM) while corresponding percentages (25-52%) of CD34+ PBPC were in the S/G2M phase of the cell cycle at the end of the transduction period. The proportion of vincristine-resistant CFU-GM was similar to the CAFC data and no significant differences were found between various MDR1-SNT transduction schedules whereas MDR1 co-cultivation, which served as a positive control, yielded significantly higher proportions of resistant colonies (5.3 ± 1.4%, IL-3, 96 hr, p ≤ 0.05). Assessment of rhodamine-123 (Rh-123) efflux in the myelo-monocytic progeny of MDR1-transduced cells mirrored the colony assay results in the SNT and co-cultivation groups. Less culture effort was required in the Rh-123 assay and functional characterization of the transferred P-glycoprotein was possible using cyclosporin A. Further development toward an effective MDR1 gene therapy should be facilitated by the CAFC assay, which allows estimation of the retroviral gene transfer frequency into primitive hematopoietic cells, and by the Rh-123 assay, which permits tractable side-by-side assessments of numerous MDR1 transduction protocols or different MDR1-SNT lots.
Elektronische Reproduktion der Druck-Ausgabe 20. März 2008
Gesehen am 14.05.2025